Propagation Characterization of the Electromagnetic Wave along with the Interface between Two Lossless Dielectric Media - Som, Bhaskar (Journal of Electronic Design Engineering, 2020)
A Transverse Electric (TE) mode of propagation having the electric field perpendicular to the interface is considered. Two media are assumed to be lossless. Phase velocities of the waves through the two media and the interface are calculated. These velocities are found to be different from the actual phase velocities in the dielectrics. The phase velocity in one dielectric is modified by the presence of another dielectric medium. The phase velocities in the two media are greater than the phase velocity of the wave along with the interface. Also, the phase velocities in the media in contact are greater than the velocities of the wave in the two media when they are separated. The wave is found to bend away from the interface in both the media. Very low loss dielectric media are practically lossless at very low frequencies. These dielectric media may be useful for Wireless Power Transmission (WPT) system. The bending property of the electromagnetic wave away from the interface and the low loss will help one to locate the receivers away from the transmitter in the WPT system. The use of very low loss dielectric media and Very Low Frequency (VLF) transmitter are suggested for efficient WPT systems.